Neonatal oxygen saturation alarm compliance –under recognized source of iatrogenic harm? An audit and survey of nursing opinion. Issue 1 (February 2020) - Harris, Sarah L.; Wolff, Emma; Beecroft, Gina; Troughton, Richard; Austin, Nicola
Abstract: Purpose: Oxygen saturation targeting aims to reduce the harm of hypoxia and hyperoxia. This study audited compliance with neonatal intensive care unit oxygen saturation alarm settings and surveyed nursing opinion to better understand factors that influence our ability to maintain infants within the recommended target range. Design: Audit of practice in a single tertiary neonatal intensive care unit followed by an anonymized survey of nursing opinion. Main outcome variable: Oxygen saturation alarm setting compliance with local oxygen saturation targeting protocol. Results: Audit of oxygen saturation alarm limit compliance revealed a high rate of non-compliance, particularly in babies on oxygen with a concerning rate of alarms set at 100% in infants <28 weeks gestation. Our survey revealed a highly skilled workforce who highlighted the challenges of maintaining infants within narrow target ranges. We propose a number of steps that could be taken that may improve oxygen saturation targeting and alarm compliance.